simplify:
(tan^2theta)/(sec^2theta)
still trying to find how to start out haha but cant seem to find out if anyone can help im really struggling with this...
Remember that $\displaystyle \sec^2{\theta} = \tan^2{\theta} + 1$
So $\displaystyle \tan^2{\theta} = \sec^2{\theta} - 1$.
Also recall that $\displaystyle \sin^2{\theta} + \cos^2{\theta} = 1$.
Therefore
$\displaystyle \frac{\tan^2{\theta}}{\sec^2{\theta}} = \frac{\sec^2{\theta} - 1}{\sec^2{\theta}}$
$\displaystyle = 1 - \frac{1}{\sec^2{\theta}}$
$\displaystyle = 1 - \cos^2{\theta}$
$\displaystyle = \sin^2{\theta}$.